Invited paper: Assessment and management of breeding bulls - Chenoweth, P. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2012)
Reproductive statistics on the farm are greatly influenced by the fertility and the handling of the bulls. Bull fertility is influenced by number and quality of spematozoids, libido and mounting skills, as well as by the social interactions between the animals in the reproductive field o corral. The procedures for evaluating a bull include the Breeding Soundness Evaluation (BSE), and tests of sexual desire and mounting skills. The new BSE criteria established by the American Society of Teriogeneology, include new standards for scrotal circumferance, motility, spermatazoon morphology. In practice, these new standards have proved to be stricter than the previous ones, affecting young Bos indicus bulls in particular. There are a series of tests to evaluate sexual desire in bulls which iriclude an evaluation of libido, and the certification of service capacity. In this artic le the repeatability of certain tests is discussed, and its relationship with reproductive efficiency and the factors which affect it, as well as the expression of sexual desire in the bull. The factors to discuss include bull breeding methods, the bull/ cow ratio, social effects and genotype differences. Since there is no relationship between sexual desire and reproductive capacity in bulls, the optimum estimation of bull breeding soundness should include the evaluation of both. To optimize bull use, they should be evaluated each year and the use of young and old bulls in the same breeding area should be avoided.